A Generational Cohort Study of the Relationship between Religious Intensity and Religious Assurance for the Purchase of Non-food Products - Ibrahim, Hifza; Ismail, Hashanah (International Journal of Economics and Financial Issues, 2015)
This paper reports on a study of a special market segment in Malaysia: a group of consumers labeled as the generational cohort of the Malaysian Gen Y consumers. The objective of this paper is to examine the influence of religion and intensity of religion in a consumer's make up on the purchase intention of nonfood products carrying the Halal label by a specific market segment. A survey of 300 Muslim Generation Y consumers as a generational cohort in the country was carried out in order to assess the intensity of religion of consumers and how this intensity relates to intention to buy non-food products like cosmetics and toiletries, which have certification of assurance that the products are Halal compliant. The study measures religious intensity by using the Religiosity Scale developed by Kraus et al. The study finds that several personal characteristics of respondents are significantly related to purchase behavior , proxied by intention to purchase for halal labeled non-food products. The study also finds a significant relationship between religiosity and purchase intention for halal labeled non-food products among Gen Y respondents. This is a new finding and therefore contributes to the limited literature on purchase behavior for Halal labeled non-food products. It also contributes to the literature on Gen Y decision making when considering purchase of non- food products which carry the Halal label. Keywords: Religiosity; Halal labeled products; generational cohort; Malaysian Gen Y's. JEL Classifications: M00